The global condition : conquerors, catastrophes and community - McNeill, William Hardy, 1917-2016 (Princeton University Press, 2017)
William H. McNeill is known for his ability to portray the grand sweep of history. The Global Condition is a classic work for understanding the grand sweep of world history in brief compass. Now with a new foreword by J.R. McNeill, this book brings together two of William Hardy McNeill's popular short books and an essay. The Human Condition provides a provocative interpretation of history as a competition of parasites, both biological and human; The Great Frontier questions the notion of "frontier freedom" through an examination of European expansion; the concluding essay speculates on the role of catastrophe in our lives.